A Headset in the Bladder - Soetojo, Soetojo; Madani, Hasan (Folia Medica Indonesiana, 2019)
Foreign objects may be present in the bladder due to deliberate insertion or displacement of the surrounding organs. There have been multiple cases of sharp objects such as nails, hair pins, and screws, as well as large objects such as AAA batteries, toothbrushes, and ballpoint pens found in the urethra and the bladder, which must have been aimed to induce sexual satisfaction associated with mental and psychic disorders. The diagnosis was established by means of radiological examinations, ie thoracic x-ray, KUB, and urethrography. This article reported a 32-year-old man with headset inserted to penile until bladder and could not be pulled out again. The patient complained pain and bleeding out of the urinary tract. We performed vesicotomy and pulling the out headset from bladder. The operation was succesful. In conclusion, the case of a headset in the bladder has been treated successfully with vesicotomy.